A comment on British imperial decline and the conditions of emergence for Scottish nationalism. Issue 1 (1st March 2013) - Davidson, Neil
Abstract : This is a reply to:McCormick, Callum. 2013. "From post-imperial Britain to post-British imperialism." Global Discourse . 3 (1): 100–114. http://dx.doi.org/10.1080/23269995.2013.804762 .